1988
DOI: 10.1007/bf00256769
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis of folate deficiency in acutely ill patients: results of a randomized clinical trial

Abstract: A trial was carried out of prophylaxis of folate deficiency in 105 acutely ill patients immediately following admission to an ICU with evaluation of folate status. These patients were fed either orally or by enteral or parenteral nutrition. Three groups were established regardless of the type of nutrition: - Group 1 received 5 mg/day parenteral folinic acid; - Group 2 received 50 mg/week parenteral folinic acid; - Group 3 received no parenteral folinic acid. Before treatment, 19% of the patients presented very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Campillo and colleagues [12] have demonstrated that 19 % of patients admitted to their ICU were deficient in folic acid upon arrival, as monitored by serum levels. Furthermore, among their patients, they have documented two cases of acute folate defiency presenting as low blood cell counts with corresponding acute changes in the bone marrow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Campillo and colleagues [12] have demonstrated that 19 % of patients admitted to their ICU were deficient in folic acid upon arrival, as monitored by serum levels. Furthermore, among their patients, they have documented two cases of acute folate defiency presenting as low blood cell counts with corresponding acute changes in the bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…We may rely on the study of Campillo et al who demonstrated that critically ill patients without folic acid supplementation had no reduction in their serum and erythrocyte folic acid concentrations over time (after 7 days of stay in the ICU) [12]. No such data are available for vitamin B6 or P-5¢-P.…”
Section: Discussionmentioning
confidence: 99%
“…Given the difficult clinical and laboratory diagnosis for both deficiencies, prophylactic administration may provide a cost-effective alternative. In a small RCT, parenteral folate at 5 mg/day appeared safe [12]. generated the hypothesis that correction of very low levels may increase survival [8].…”
Section: Vitamin C and Vitamin D Repletionmentioning
confidence: 99%
“…Other contributing factors include disseminated intravascular coagulation (DIC), pathogen-associated hemolysis, hypoadrenalism, and nutritional deficiency. [56][57][58] Figure 3. Sepsis and the acute phase response result in anemia of inflammation, characterized by iron sequestration in monocytes/macrophages, decreased erythropoietin (Epo) production, and blunted bone marrow response to Epo.…”
Section: Anemiamentioning
confidence: 99%